Problems of Rational Placing Organisations and Specialization of Agricultural Production in RA - Manasyan, Volodya (Journal of Sociology: Bulletin of Yerevan University, 2017)
In this article, the problems of rational accommodation and specialization of agricultural production in RA are discussed. The dependence of these factors upon placing of big cities and industrial centres, the necessity of transportation expenses calculation as well as a number of social-ecologoeconomic factors promoting or impeding the concentration of agricultural production in our Republic are emphasized.